2017
DOI: 10.3390/nu9111207
|View full text |Cite
|
Sign up to set email alerts
|

What Should Be Taught in Secondary Schools’ Nutrition and Food Systems Education? Views from Prominent Food-Related Professionals in Australia

Abstract: Education can help young people to attain the knowledge and the skills that they need to make proper food choices and develop lifelong healthy eating patterns. This study explored the perspectives of prominent food-related professionals in Australia regarding essential nutrition and food systems (N&FS) education programs for adolescents during formal education. Semi-structured interviews were conducted with 21 prominent food-related professionals in Australia. Interview transcripts were analysed thematically. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
0
18
0
4
Order By: Relevance
“…People's daily diet intake is influenced by their habits acquired since childhood (19). Schools and other education settings have long been considered a primary target to deliver nutrition education (20). Proper nutrition is essential for the physical and mental development of children and adolescents, which means school children are at the phase of life when they are adapting habits that will last a lifetime; and children are an important link among school, home, and community (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People's daily diet intake is influenced by their habits acquired since childhood (19). Schools and other education settings have long been considered a primary target to deliver nutrition education (20). Proper nutrition is essential for the physical and mental development of children and adolescents, which means school children are at the phase of life when they are adapting habits that will last a lifetime; and children are an important link among school, home, and community (21).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-three (41.3%), 24 (23.1%), and 6 (5.8%) of the respondents did physical activities regularly, tried to lose weight, and never took sweetened food or drinks, respectively. Only 26.0% (27), and 19.2% (20) of the respondents were concerned about reducing fat and calories in their diet and had the blood test done for T2DM, respectively. Furthermore, 17.3% (18) of them always consumed sweet food and drinks, which is not a healthy practice.…”
Section: Practice Of Respondents Regarding T2dmmentioning
confidence: 99%
“…A previous study showed that older individuals have more interest in chronic health-related topics over younger individuals [8], but to our knowledge no other studies have shown similar findings. Although, educators agree that how nutrition leads to a healthy lifestyle and healthy food choices are important teaching topics [14,30].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, targeting children in primary school was seen by stakeholders as being fundamental in the development of future education policies. Not only education through the provision of healthy canteens, but also via the Department of Education's school curriculum, where children are influenced for the future, but also their families by their children taking home the information (Sadegholvad, Yeatman, Parrish, & Worsley, 2017;Story, Nanney, & Schwartz, 2009).…”
Section: Policy Issue For Prioritisationmentioning
confidence: 99%
“…Future-proofing the habits of children is imperative in response to the changing social environment, including the increased use of technology and social media (Witten & Pearce, 2016). Empowering children, and youth, not only with the knowledge of food and nutrition, but also with the skills to be able to make the right choices was emphasised (Sadegholvad et al, 2017). Educating people about the practicality of being able to cook, the different types of food, knowing where your food comes from, how to use your foods, and the balance between core foods and discretionary foods.…”
Section: Policy Issue For Prioritisationmentioning
confidence: 99%